Communication within Banking Organizations and Small Business Lending. (20th March 2020) - Levine, Ross; Lin, Chen; Peng, Qilin; Xie, Wensi
Abstract: We investigate how communication within banks affects small business lending. Using travel times between a bank's headquarters and its branches to proxy for the costs of communicating soft information, we exploit shocks to these travel times—the introduction of new airline routes—to evaluate the impact of within-bank communication costs on small business loans. We find that reducing headquarters-branch travel time boosts small business lending in the branch's county. Several extensions suggest that new airline routes facilitate in-person communications that boost small-firm lending.